Analisis Bentuk Kesalahan dalam Mengarang Bahasa Jepang yang Dipengaruhi oleh Bahasa Pertama - Lispridona Diner (JLA (Jurnal Lingua Applicata), 2019)
Second language acquisition (SLA) for Indonesian students can be in the form of regional languages, Indonesian language, English as an international language or a foreign language. Foreign languages such as Mandarin, Korean and Japanese. The learning process of writing especially at the elementary level, students have difficulty in composing Japanese sentences. Based on observations, this happens because in the process of writing students are still influenced by the first language. Therefore, this study aims to determine the effect of first language in writing Japanese at the elementary level. The research method used in this study is a qualitative research method. The data of this research are in the form of students' essays in the Shokyuu Kohan sakubun course. And the data analysis technique used is the analysis of language errors. Based on the results and discussions, it can be concluded that writing Japanese essays is influenced by the first language, in this case the first language is Indonesian. Of the errors affected by the first language by 67% influenced by the sentence patterns of the first language and 33% influenced by the vocabulary of the first language.